(untitled) (Research, Society and Development, 2022)
Introduction: Existing evidence suggests that the human reproductive system may be potentially vulnerable to infection with the novel coronavirus. However, the association between SARS-CoV-2 infection and reproductive health is currently poorly understood. Objective: To analyze and synthesize key information regarding the effect of SARS-CoV-2 infection on male fertility. Methods: Integrative literature review that performed searches in Medical Literature Analysis and Retrieval System Online, Scientific Electronic Library Online, and Latin American and Caribbean Literature on Health Sciences Information, between December 2021 and June 2022, with the descriptors "SARS-CoV-2," "sperm," "semen," and "infertility, male," that sought to answer the question, "What relationship exists between SARS-CoV-2 infection and male fertility?" The search resulted in 454 articles, of which 13 were selected because they met the eligibility criteria. Results: The presence of viral ribonucleic acid was not detected in the semen of men recovered from COVID-19, however, a decrease in sperm count and concentration was evidenced, as well as a reduction in their motility and macroscopic changes in the semen, factors that may hinder fertilization. Conclusion: The male reproductive system may be potentially vulnerable to infection by SARS-CoV-2, highlighting the importance of instituting actions that ensure comprehensive assistance to men’s reproductive health after infection.